Ryzyko regulacyjne projektu unii bankowej. Polska perspektywa - Kasiewicz, Stanisław (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The paper focuses on the identification and assessment of regulatory risk of thebiggest European Union’s project – Banking Union. Two approaches are usedto assess regulatory risk. The first one considers risk arising from Poland’s refusalto accede to the Banking Union. The second one considers opportunities arisingfrom the formal and active membership of Poland in this treaty. The results supportthe case for Poland’s membership in the Banking Union. The most importantargument for membership is increasing the resistance of the Polish banking sectorto high or very high systematic risks.